Foraminifera in temperate fjords strongly affected by glacial meltwater, Tierra del Fuego, South America - Korsun, Sergei; Kniazeva, Olga; Majewski, Wojciech; Godoi Millan, Maria Angelica; Hromic, Tatiana; Varfolomeeva, Marina; Pawlowski, Jan (My University, 2023)
Chilean Patagonia is one of the few regions in the Southern Hemisphere where tidewater glaciers deliver torrential meltwater. We sampled the Beagle Channel and five tributary fjords, with and without glaciers, to explore modern foraminifera of this little studied region. Surface sediments (mud, sand, pebbles, and shell debris) were collected at 45 stations from water depths 15 to 250 m, along with four short cores. The soft bottom recovered at 35 stations was analyzed for grain size, Loss-on-ignition reflecting content of organic matter, and Rose-Bengal-stained foraminifera. The benthic fauna consisted of 86 attached and free-living species. Uvigerina bifurcata, Alveolophragmium orbiculatum, Ammobaculites americanus, Stainforthia fusiformis, Globobulimina noto-vata, and Nonionoides grateloupii were dominant. As shown by downcore distribution, U. bifurcata and A. orbiculatum occupied epifaunal and G. notovata and S. fusiformis infaunal microhabitats. Distribution of the dominant foraminifera showed no clear pattern, with the exception of S. fusiformis, which formed a monospecific assemblage in sediments enriched with organic matter. Certain subdominant species, including Cassidulinoides parkerianus, Pullenia subcarinata, and Cibicides fletcheri, showed environmental affinity to more sandy sediments, whereas the assemblage from more muddy sediments had no inherent taxa. Foraminiferal standing crop in size fraction >125 mu m was mostly 100 to 500 specimens per 10 cm3 but dropped to <1 specimen near glacier fronts, where foraminifera varied greatly between stations and did not constitute a single, unified assemblage. This patchy pattern seems to result from environmental instability caused by rapidly settling mineral fines and from random dispersal and activation of propagules. It helps to interpret records of other meltwater-dominated events.
Keywords: turbid meltwater; tidewater glacier; environmental instability; southern patagonia; beagle channel